2020
DOI: 10.1177/1557988320975541
|View full text |Cite
|
Sign up to set email alerts
|

The Price of Playing Through Pain: The Link Between Physical and Behavioral Health in Former NFL Athletes

Abstract: Over the past decade, media outlets have drawn attention to some of the health consequences of playing in the National Football League (NFL), including how wear-and-tear and injuries accumulated during athletes’ playing years can affect their physical, emotional, and behavioral health after retirement from professional sports. Through a secondary analysis of a cross-sectional telephone survey of former NFL athletes, this study estimated logistic regression models to assess the relationship between several form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Athletes 'physical health is also another determining concept to take into account before, during and after the conclusion of the sports career, as the review suggests that athletes who have been forced to retire due to injuries tend to develop more mental and quality of life problems than those athletes who ended their sports career intentionally (Sanders & Stevinson, 2017). Furthermore, we can affirm that after reviewing these publications, the frequency of injuries alongside poor care and treatment can have long-term repercussions on the athlete's well-being (Bush et al, 2020).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Athletes 'physical health is also another determining concept to take into account before, during and after the conclusion of the sports career, as the review suggests that athletes who have been forced to retire due to injuries tend to develop more mental and quality of life problems than those athletes who ended their sports career intentionally (Sanders & Stevinson, 2017). Furthermore, we can affirm that after reviewing these publications, the frequency of injuries alongside poor care and treatment can have long-term repercussions on the athlete's well-being (Bush et al, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…Many authors with similar methodological objectives choose different measurement instruments, with a clear preference over short versions. On the other hand, the sample acceptance ratio in this type of study is around 30% of the total population contacted (Torregrossa et al, 2019), with certain exceptions in some studies with an acceptance ratio greater than 60% (Bush et al, 2020).…”
Section: Content Indicator Thematic Trends and Measurement Instrumentsmentioning
confidence: 89%
See 2 more Smart Citations
“…This may be because LSB is more likely to cause an increase in disc compression force [36] and long-term overload of lumbar muscles, resulting in functional disorders, loss of stability, and changes in physiological radian of the entire lumbar vertebra, ultimately leading to LBP. Drinking and smoking are considered as risk factors for cervicalgia and LBP, [3,[37][38][39][40] and their mechanism may be attributed to the disturbance of intervertebral disc microcirculation. Palmer et al [41] concentrated on the morbidity and occupational factors of 993 patients with neck pain in the UK, and confirmed that smoking has an inducing effect on cervicalgia.…”
Section: Discussionmentioning
confidence: 99%